Polyolefin composite material as well as preparation method and application thereof

By using polyolefin composite materials in cable materials, combined with barriers, epoxy resins and antioxidants, the problem of insufficient thermal oxygen aging performance of cable materials in harsh environments is solved, and the material's precipitation resistance and thermal oxygen aging resistance are achieved, ensuring stable performance of the cable when used in harsh environments.

CN119752019APending Publication Date: 2025-04-04KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411954552.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When used in harsh environments and weather conditions, the thermal oxygen aging performance is insufficient, and the additives are severely precipitated, which affects the long-term use of the material.

Method used

Polyolefin composite materials are used to reduce additive precipitation and improve oxygen shielding efficiency by adding barriers, epoxy resins and antioxidants, and inorganic fillers.

Benefits of technology

The precipitation resistance and thermal oxygen aging resistance of polyolefin composite materials are achieved, ensuring stable performance of cables when used in harsh environments and extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215556820000131
    Figure BDA0005215556820000131
  • Figure BDA0005215556820000132
    Figure BDA0005215556820000132
  • Figure BDA0005215556820000141
    Figure BDA0005215556820000141
Patent Text Reader

Abstract

The invention provides a polyolefin composite material as well as a preparation method and application thereof, and the polyolefin composite material comprises the following components in parts by weight: 20-50 parts of an ethylene polymer, 40-52 parts of an inorganic filler, 0.1-5 parts of a blocking agent, 0.2-1.8 parts of epoxy resin and 0.2-2 parts of an antioxidant. According to the invention, the polyolefin composite material resists precipitation of an auxiliary agent and has good thermo-oxidative aging performance; therefore, the cable comprising the polyolefin composite material can be used in severe environments and weather.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polyolefin composite material and a preparation method and application thereof. Background Art

[0002] Wires and cables, also referred to as cables, are wire products used to transmit electrical (magnetic) energy, information and realize electromagnetic energy conversion. They are widely used in rail transit, transportation, communications, construction, energy, ships, automobiles and other fields. With the development of society, the use of cables is increasing, not only for indoors, but also for outdoors. When used outdoors, cables will be affected by various harsh environments and weather, such as high and low temperatures, strong ultraviolet radiation, high ozone concentrations, chemical corrosion and other environments; and harsh environments and weather will cause the performance of cables to deteriorate, and in severe cases, fires will occur, affecting the safety of life and property.

[0003] In order to meet the requirements of cable materials used in harsh environmental conditions, the industry is actively developing high-efficiency heat-oxidation-resistant cable materials. Usually, antioxidants are added to the formula to improve the aging resistance of cable materials. However, as the use time increases, antioxidants and other additives will precipitate, resulting in whitening and severe frosting on the surface of the material, which affects the use of the product and, in the medium and long term, also affects its ultimate weather resistance.

[0004] Patent US5449711A discloses preventing the blooming phenomenon on the surface of products molded from olefin thermoplastic elastomer compositions by compounding one or more compounds selected from polyol esters and alkyl alkanolamines into elastomers. However, the above patent does not take into account the aging resistance of the material while inhibiting the precipitation of the auxiliary agent.

[0005] Therefore, developing a cable material that has both precipitation resistance and good thermal oxygen aging resistance is an issue that needs to be urgently addressed in the art. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a polyolefin composite material and a preparation method and application thereof. The polyolefin composite material is resistant to precipitation of additives and has good thermal oxidative aging performance, so that the cable including the polyolefin composite material can be used in harsh environments and weather.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a polyolefin composite material, which comprises, by weight, 20 to 50 parts of ethylene polymer, 40 to 52 parts of inorganic filler, 0.1 to 5 parts of barrier agent, 0.2 to 1.8 parts of epoxy resin and 0.2 to 2 parts of antioxidant.

[0009] In the present invention, by adding a barrier agent and epoxy resin and an antioxidant for compounding, the precipitation of the antioxidant can be reduced and the oxygen shielding efficiency can be improved; at the same time, the addition of inorganic fillers can also reduce the precipitation of auxiliary agents and improve the oxygen shielding rate, so that the polyolefin composite material has both precipitation resistance and thermal oxygen aging resistance.

[0010] In the present invention, 20 to 50 parts of ethylene polymers can be, for example, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts or a range between any of the above values; more preferably 25 to 45 parts.

[0011] In the present invention, 40 to 52 parts of inorganic filler can be, for example, 40 parts, 40.2 parts, 40.5 parts, 40.8 parts, 41 parts, 41.2 parts, 41.5 parts, 41.8 parts, 42 parts, 42.2 parts, 42.5 parts, 42.8 parts, 43 parts, 43.2 parts, 43.5 parts, 43.8 parts, 44 parts, 44.2 parts, 44.5 parts, 44.8 parts, 45 parts, 45.2 parts, 45.5 parts, 45.8 parts, 46 parts, 46.2 parts, 46.5 parts, 46.8 parts, 47 parts, 47.2 parts, 47.5 parts, 47.8 parts, 48 ​​parts, 48.2 parts, 48.5 parts, 48.8 parts, 50 parts, 51 parts, 52 parts or the range between any of the above values.

[0012] In the present invention, 0.1 to 5 parts of the barrier agent can be, for example, 0.1 part, 0.2 part, 0.3 part, 0.35 part, 0.4 part, 0.45 part, 0.5 part, 0.55 part, 0.6 part, 0.65 part, 0.7 part, 0.75 part, 0.8 part, 0.85 part, 0.9 part, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts or a range between any of the above values; more preferably 0.15 to 2 parts, and particularly preferably 0.2 to 1 part.

[0013] In the present invention, 0.2 to 1.8 parts of epoxy resin can be, for example, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.64, 0.6 6 parts, 0.68 parts, 0.7 parts, 0.72 parts, 0.74 parts, 0.76 parts, 0.78 parts, 0.8 parts, 0.82 parts, 0.84 parts, 0.86 parts, 0.88 parts, 0.9 parts, 0.92 parts, 0.94 parts, 0.96 parts, 0.98 parts, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or a range between any of the above values; more preferably 0.3-1.6 parts, particularly preferably 0.55-1.45 parts.

[0014] In the present invention, 0.2 to 2 parts of antioxidant can be, for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts or any range between the above values.

[0015] Preferably, the ethylene-based polymer includes at least one of ethylene-vinyl acetate copolymer (EVA), linear low-density polyethylene (LLDPE) or polyolefin elastomer (POE).

[0016] Preferably, the ethylene polymer comprises, by weight, 15 to 25 parts of ethylene-vinyl acetate copolymer (for example, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 or any range between the above values), 1 to 10 parts of linear low density polyethylene (for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or any range between the above values), and 4 to 15 parts of polyolefin elastomer (for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or any range between the above values).

[0017] In the present invention, the ethylene-vinyl acetate copolymer (EVA) has a melt index of 0.3 to 10 g / 10 min at 190° C. and 2.16 kg, for example, 0.3 g / 10 min, 0.5 g / 10 min, 1 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min, 9 g / 10 min, 10 g / 10 min or a range between any of the above values.

[0018] In the present invention, the linear low density polyethylene (LLDPE) has a melt index of 1 to 10 g / 10 min at 190° C. and 2.16 kg, for example, 0.3 g / 10 min, 0.5 g / 10 min, 1 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min, 9 g / 10 min, 10 g / 10 min or a range between any of the above values.

[0019] In the present invention, the melt index test is performed according to the standard ASTMD1238; specifically, the plastic pellets are first melted into a plastic fluid, and then within a certain time (10 minutes), a certain temperature and pressure (different standards for various materials), after flowing out through a 2.1mm diameter round tube, the gram (g) is measured. The larger the value, the better the processing fluidity of the material, and vice versa.

[0020] In the present invention, the polyolefin elastomer includes ethylene-butene copolymer and / or ethylene-octene copolymer; the polyolefin elastomer includes a polyolefin elastomer prepared by using a metallocene catalyst.

[0021] In the present invention, the melt index of the polyolefin elastomer at 190°C and 2.16kg is 0.3-20g / 10min, for example, it can be 0.3g / 10min, 0.5g / 10min, 1g / 10min, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min, 10g / 10min, 12g / 10min, 14g / 10min, 16g / 10min, 18g / 10min, 20g / 10min or a range between any of the above values.

[0022] Preferably, the surface of the inorganic filler is coated with at least one of an amine compound, silane or stearic acid.

[0023] Preferably, the amine compound includes a quaternary ammonium salt and / or an amide compound.

[0024] Preferably, the silane comprises at least one of vinyl silane, amino silane, epoxy silane or polysilicate.

[0025] Preferably, the inorganic filler comprises aluminum hydroxide and / or magnesium hydroxide.

[0026] In the present invention, the D50 particle size of the inorganic filler is 0.5 to 5 μm, for example, it can be 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5 μm or the range between any of the above values.

[0027] In the present invention, the inorganic filler can be interface modified and the surface of the inorganic filler can be coated with amine compounds, silane or stearic acid, etc., which is beneficial to improve the compatibility of the inorganic filler with the matrix resin, reduce the precipitation channels of the additives, and improve the oxygen shielding rate, thereby taking into account the precipitation resistance and heat-oxidation aging resistance of the polyolefin composite material.

[0028] Preferably, the barrier agent comprises an inorganic substance having a layered structure.

[0029] Preferably, the barrier agent comprises at least one of intercalated montmorillonite, hydrotalcite, talc or kaolin.

[0030] Preferably, the D50 particle size of the barrier agent is 0.05 to 0.3 μm, for example, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.11 μm, 0.12 μm, 0.13 μm, 0.14 μm, 0.15 μm, 0.16 μm, 0.17 μm, 0.18 μm, 0.19 μm, 0.2μm, 0.21μm, 0.22μm, 0.23μm, 0.24μm, 0.25μm, 0.26μm, 0.27μm, 0.28μm, 0.29μm, 0.3μm or a range between any of the above values, more preferably the D50 particle size is 0.121~0.201μm, and particularly preferably the D50 particle size is 0.125~0.142μm.

[0031] Preferably, the epoxy resin comprises an epoxy resin grafted with an ester compound containing a carbon-carbon double bond.

[0032] Preferably, the carbon-carbon double bond-containing ester compound includes vinyl acetate and / or ethyl acrylate.

[0033] Preferably, the grafting rate of the carbon-carbon double bond ester compound grafted onto the epoxy resin is 0.5-2.5%, for example, it can be 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% or the range between any of the above values, and the more preferred grafting rate is 1-2%.

[0034] Preferably, the epoxy resin comprises vinyl acetate grafted epoxy resin and / or ethyl acrylate grafted epoxy resin.

[0035] Preferably, the mass ratio of the antioxidant, the barrier agent and the epoxy resin is 1:(0.1-2):(0.2-2.5), wherein the specific value in (0.1-2) can be, for example, 0.1, 0.15, 0.2, 0.25, 0.3, 0.33, 0.35, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.75, 0.78, 0.8, 0.85, 0.9, 0.95, 1, 1.1, 1.2, 1.4, 1.6, 1.8, 2 or the range between any of the above values; .2~2.5) can be, for example, 0.2, 0.3, 0.4, 0.5, 0.6, 0.67, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5 or the range between any of the above values; more preferably, the mass ratio of antioxidant, barrier agent and epoxy resin is 1:(0.3~1):(0.6~1.6).

[0036] Preferably, the antioxidant includes at least one of a hindered phenol antioxidant, a thioester antioxidant or a phosphite antioxidant.

[0037] Preferably, the antioxidant comprises a composite antioxidant comprising a hindered phenol antioxidant as a main antioxidant and a thioester antioxidant and / or a phosphite antioxidant as an auxiliary antioxidant; the mass ratio of the main antioxidant to the auxiliary antioxidant is (1-3):1, wherein the specific values ​​in (1-3) can be, for example, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3 or a range between any of the above values.

[0038] Preferably, the polyolefin composite material further comprises 2 to 16 parts by weight of other additives, for example, 2 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts or a range between any of the above values.

[0039] Preferably, the other auxiliary agent includes at least one of a compatibilizer, a dispersant or a colorant.

[0040] Preferably, the compatibilizer comprises maleic anhydride grafted modified metallocene polyethylene.

[0041] In the present invention, the maleic anhydride grafted modified metallocene polyethylene has a melt index of 0.5 to 4 g / 10 min at 190° C. and 2.16 kg, for example, 0.5 g / 10 min, 1 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min or any range between the above values.

[0042] Preferably, the dispersant comprises an organosiloxane polymer.

[0043] In the present invention, the organosiloxane polymer includes an ultra-high molecular weight organosiloxane polymer, and the mass percentage of siloxane in the ultra-high molecular weight organosiloxane polymer is 40-60%, for example, it can be 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60% or any range between the above values; the ultra-high molecular weight refers to a weight average molecular weight of 1 million to 1.5 million.

[0044] Preferably, the colorant comprises carbon black.

[0045] In the present invention, the carbon black is in the form of carbon black masterbatch, and the mass percentage of carbon black in the carbon black masterbatch is ≥48%, for example, it can be 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80% or any range between the above values; the carbon black dispersion in the carbon black masterbatch is ≤ grade 3; the resin matrix of the carbon black masterbatch includes polyolefin.

[0046] Preferably, the polyolefin composite material comprises, by weight, 1 to 6 parts of a compatibilizer (for example, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts, 4.8 parts, 5 parts, 5.5 parts, 6 parts or any range between the above values), 1 to 6 parts of a dispersant (for example, 1 part, 1.2 parts, 1.4 parts, 1.6 parts , 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts, 4.8 parts, 5 parts, 5.5 parts, 6 parts or ranges between any of the above values) and 0.5 to 3 parts of carbon black (for example, 0.5 parts, 0.6 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.7 parts, 3 parts or ranges between any of the above values).

[0047] In the present invention, lubricants, acid absorbers, etc. can also be added as needed; the lubricants include erucamide, ethylene bisstearamide, ethylene wax or white oil, etc.; the acid absorbers include magnesium hydroxide, zinc oxide, zinc stearate, etc.

[0048] In a second aspect, the present invention provides a method for preparing the polyolefin composite material according to the first aspect, the preparation method comprising the following steps:

[0049] The polyolefin composite material is obtained by mixing and extruding an ethylene polymer, an inorganic filler, a barrier agent, an epoxy resin and an antioxidant.

[0050] Preferably, the mixed material further comprises other auxiliary agents.

[0051] In the present invention, the mixing includes: adding ethylene polymer, inorganic filler, epoxy resin and optional compatibilizer and dispersant into a high-speed mixer and mixing them evenly at a speed of 2000-3000 rpm, adding an optional lubricant and mixing them at a speed of 1000-3000 rpm for 1-3 minutes, and then adding an antioxidant, a barrier agent, a carbon black masterbatch and an optional acid absorber in a high-speed mixer and mixing them evenly at a speed of 500-1500 rpm.

[0052] Preferably, the extrusion temperature is 180-220°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C or any range between the above values.

[0053] In the present invention, the extrusion is carried out in a twin-screw extruder; the aspect ratio of the twin-screw extruder is 44-50:1; and the temperature of each zone of the twin-screw extruder is 180-220°C.

[0054] In a third aspect, the present invention provides a cable, comprising the polyolefin composite material described in the first aspect.

[0055] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] The polyolefin composite material provided by the present invention can reduce the precipitation of the antioxidant and improve the oxygen shielding efficiency by adding a barrier agent and an epoxy resin and using it in combination with an antioxidant; at the same time, the addition of an inorganic filler can also reduce the precipitation of the auxiliary agent and improve the oxygen shielding rate, so that the polyolefin composite material has both precipitation resistance and thermal oxygen aging resistance. DETAILED DESCRIPTION

[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0059] The materials used in the present invention can be obtained by commercially available or conventional preparation methods. Unless otherwise specified, the materials used in the present invention are as follows:

[0060] Ethylene polymers

[0061] EVA: EVA V5120J, Jiangsu Sailbon Petrochemical Co., Ltd.

[0062] LLDPE: LLDPE DFDA-7042, Wanhua Chemical.

[0063] POE: SOLUMER 891, SK, South Korea.

[0064] Inorganic fillers

[0065] A1: Aluminum hydroxide modified by amine compounds, Aitemina 140FF, Jiangsu Aitek Flame Retardant Materials Co., Ltd.

[0066] A2: Silane modified aluminum hydroxide, Aitemina 140FD, Jiangsu Aitek Flame Retardant Materials Co., Ltd.

[0067] A3: Stearic acid modified aluminum hydroxide, Aitemina 140ZA, Jiangsu Aitek Flame Retardant Materials Co., Ltd.

[0068] A4: Amine compound modified magnesium hydroxide, H-5IV, Jiangsu Wannapu New Material Technology Co., Ltd.

[0069] A5: Unmodified aluminum hydroxide, Aitemina 140, Jiangsu Aitek Flame Retardant Materials Co., Ltd.

[0070] Barrier

[0071] B1: hydrotalcite, D50 particle size is 0.128μm, AZ-128 from Chenghe Technology.

[0072] B2: hydrotalcite, D50 particle size of 0.137 μm, AC-106, Chenghe Technology.

[0073] B3: hydrotalcite, D50 particle size 0.1 μm, ground AZ-128, Chenghe Technology.

[0074] B4: hydrotalcite, D50 particle size of 0.208 μm, AC-390, Chenghe Technology.

[0075] B5: montmorillonite, D50 particle size 0.128 μm, I.44P (16-20 μm) after grinding, Nanocor Inc.

[0076] B6: talc, D50 particle size 0.128 μm, ground TYT-777A, Beihai Group.

[0077] In the present invention, the particle size of the barrier agent can be tested by a laser particle size analyzer.

[0078] Epoxy resin

[0079] C1: Vinyl acetate grafted epoxy resin, grafting rate 1.2%, homemade.

[0080] The preparation method of C1 comprises: adding 200g of bisphenol A epoxy resin (YD-019, purchased from Dongdu Chemical) into a four-necked flask, adding 1 / 3 of the prepared xylene solution of vinyl acetate (the mass fraction of vinyl acetate in the xylene solution of vinyl acetate is 40%, including 38g of xylene and 25.3g of vinyl acetate), and then adding 0.3% of initiator BPO (based on the weight of the epoxy resin), starting stirring to fully mix the materials, heating and heating to 80°C under the protection of nitrogen, keeping the temperature for reaction for 30 minutes, and then starting to evenly add the remaining xylene solution of vinyl acetate, and controlling the addition to be completed within 1.5h. After the monomer is added dropwise, continue to keep the temperature at 80°C for 3h and then cool to room temperature, add xylene solution, seal and store, and use a rotary evaporator to concentrate and remove xylene under room temperature vacuum (vacuum degree is 0.09MPa) to obtain the vinyl acetate grafted epoxy resin C1.

[0081] In the present invention, the method for determining the grafting rate includes: firstly dissolving the grafted epoxy resin in xylene, refluxing and dissolving for 1 hour, pouring into excess acetone for precipitation, standing for a period of time, and the precipitation is complete. After adding acetone several times, the precipitate is filtered several times, and then standing in a 70°C vacuum oven to dry for 2 hours for standby use; accurately weighing 0.15g of the purified grafted epoxy resin, putting it into 100mL of xylene, adding 2-3 drops of deionized water and 2-3 drops of DMF to promote the hydrolysis of the ester group to generate a carboxylic acid group, refluxing and dissolving for 1 hour, and titrating with a 0.05mol / L KOH-ethanol standard solution (prepared according to the GB / T601-2002 method), using a phenolphthalein-ethanol solution as an indicator, and using no grafted epoxy resin as a blank experiment. The grafting rate is calculated according to the following formula:

[0082] ω%=100%×(V1-V0)×C×M / W.

[0083] Wherein: ω% is the grafting rate of the grafted epoxy resin.

[0084] V0: The volume of KOH-ethanol standard solution consumed by the blank sample.

[0085] V1: Volume of KOH-ethanol standard solution consumed by grafted epoxy resin sample.

[0086] C: molar concentration of KOH-ethanol standard solution, mol / L.

[0087] M: The molecular weight of vinyl acetate is 86.09 or the molecular weight of ethyl acrylate is 100.12.

[0088] W: the mass of vinyl acetate grafted epoxy resin or ethyl acrylate grafted epoxy resin.

[0089] C2: Vinyl acetate grafted epoxy resin, grafting rate 1.8%, homemade.

[0090] The preparation method of C2 is different from that of C1 only in that the mass fraction of vinyl acetate in the xylene solution of vinyl acetate is changed to 45%, including 38g of xylene and 31g of vinyl acetate, and the rest is the same as the preparation method of C1.

[0091] C3: Vinyl acetate grafted epoxy resin, grafting rate 0.6%, homemade.

[0092] The preparation method of C3 is different from that of C1 only in that the mass fraction of vinyl acetate in the xylene solution of vinyl acetate is changed to 30%, including 38g of xylene and 16.3g of vinyl acetate, and the content of initiator BPO is changed to 0.2%. The rest is the same as the preparation method of C1.

[0093] C4: Vinyl acetate grafted epoxy resin, grafting rate 2.3%, homemade.

[0094] The preparation method of C4 is different from that of C1 only in that the mass fraction of vinyl acetate in the xylene solution of vinyl acetate is changed to 48%, including 38g of xylene and 36g of vinyl acetate, and the content of initiator BPO is changed to 0.35%. The rest is the same as the preparation method of C1.

[0095] C5: Ethyl acrylate grafted epoxy resin, grafting rate 1.2%, homemade.

[0096] The preparation method of C5 is different from that of C1 only in that vinyl acetate is replaced by ethyl acrylate, and the mass fraction of ethyl acrylate in the xylene solution of ethyl acrylate is 40%, including 38g of xylene and 25.3g of ethyl acrylate. The rest is the same as the preparation method of C1.

[0097] C6: Bisphenol A epoxy resin, YD-019, Dongdu Chemical.

[0098] Poly(isophthalamide adipate) (MXD6): M30, purchased from Shanghai Yinggu Co., Ltd.

[0099] Antioxidant: A composite antioxidant composed of a hindered phenol antioxidant and a thioester antioxidant in a mass ratio of 2:1; the hindered phenol antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010); the thioester antioxidant is lauryl thiodipropionate.

[0100] Compatibilizer: Maleic anhydride grafted modified metallocene polyethylene, MC218, Ningbo Nengzhiguang New Materials Technology Co., Ltd.

[0101] Dispersant: Ultra-high molecular weight organosiloxane polymer, of which the siloxane mass content is 55%, GT-300, Zhejiang Jiahua Essence.

[0102] Carbon black masterbatch: The base resin is PE; the carbon black mass percentage is 50%, and the carbon black dispersion is ≤ level 3.

[0103] Examples 1 to 21, Comparative Examples 1 to 6

[0104] Examples 1 to 21 and Comparative Examples 1 to 6 respectively provide a polyolefin composite material, and the formulas of the polyolefin composite materials are shown in Tables 1 to 4, in parts by weight; wherein, “ / ” indicates that the component is not included in the formula; antioxidant: barrier agent: epoxy resin represents the mass ratio of the three; the carbon black content refers to the weight of pure carbon black, excluding the matrix resin in the masterbatch.

[0105] The preparation method of the polyolefin composite material comprises: putting LLDPE, POE, EVA, epoxy resin, inorganic filler, compatibilizer and dispersant into a high-speed mixer in proportion and mixing them evenly at a speed of 2500 rpm, adding lubricant 10# white oil and mixing them at a speed of 2000 rpm for 2 minutes, then adding antioxidant, barrier agent and carbon black masterbatch and mixing them evenly at a speed of 1000 rpm in a high-speed mixer, extruding and granulating the obtained mixture through a twin-screw extruder, the twin-screw aspect ratio (L / D) is 48:1, and the temperature of each zone is 180-200°C. Among them, T1 is 180°C, T2-T7 are all 200°C, and T8 is 180°C.

[0106] Table 1

[0107]

[0108]

[0109] Table 2

[0110]

[0111]

[0112] Table 3

[0113]

[0114]

[0115] Table 4

[0116]

[0117] Performance Testing

[0118] The following tests were performed on the polyolefin composite particles provided in Examples 1 to 21 and Comparative Examples 1 to 4, which were hot-pressed into sheets with a thickness of 1 mm; wherein, when testing the tensile strength and elongation at break, the sheets were cut into dumbbell shapes for testing.

[0119] (1) Initial tensile strength and initial elongation at break: measured according to the method of standard GB / T 1040.3-2018.

[0120] (2) Resistance to heat and oxygen aging: The polyolefin composite material was aged in an air atmosphere at 180°C for 168 h. The tensile strength and elongation at break of the polyolefin composite material after aging were tested according to standard GB / T 1040.3-2018. The tensile strength retention rate and elongation at break retention rate were calculated. Retention rate = tensile strength after aging (elongation at break after aging) / initial tensile strength (initial elongation at break). The higher the retention rate, the better the resistance to heat and oxygen aging.

[0121] (3) Precipitation resistance: The polyolefin composite material was placed at a temperature of 85°C and a humidity of 85% for 1000 h, and the surface of the material was observed to see whether there was precipitation of additives. No precipitation of additives was recorded as 0, and the part of the precipitated additives that accounted for less than 1% of the total material area was recorded as 1; the part of the precipitated additives that accounted for 1-5% of the total material area was recorded as 2; and the part of the precipitated additives that accounted for 5% or more of the total material area was recorded as 3.

[0122] The specific test results are shown in Table 5.

[0123] Table 5

[0124]

[0125]

[0126] As shown in Table 5, the polyolefin composite material provided by the present invention has both thermal oxidation resistance and precipitation resistance by adding epoxy resin and barrier agent. The tensile strength of the polyolefin composite material is ≥13MPa, and the elongation at break is ≥370%; the tensile strength retention rate after thermal oxidation aging is ≥72%, and the elongation at break retention rate is ≥70%.

[0127] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A polyolefin composite material, characterized in that: The polyolefin composite material comprises, by weight, 20 to 50 parts of ethylene polymer, 40 to 52 parts of inorganic filler, 0.1 to 5 parts of barrier agent, 0.2 to 1.8 parts of epoxy resin and 0.2 to 2 parts of antioxidant.

2. The polyolefin composite material according to claim 1, characterized in that: The ethylene polymer includes at least one of ethylene-vinyl acetate copolymer, linear low-density polyethylene or polyolefin elastomer; Preferably, the ethylene polymer comprises 15 to 25 parts of ethylene-vinyl acetate copolymer, 1 to 10 parts of linear low-density polyethylene and 4 to 15 parts of polyolefin elastomer, based on parts by weight.

3. The polyolefin composite material according to claim 1 or 2, characterized in that: The surface of the inorganic filler is coated with at least one of an amine compound, silane or stearic acid; Preferably, the amine compound includes a quaternary ammonium salt and / or an amide compound; Preferably, the silane comprises at least one of vinyl silane, amino silane, epoxy silane or polysilicate; Preferably, the inorganic filler comprises aluminum hydroxide and / or magnesium hydroxide.

4. The polyolefin composite material according to any one of claims 1 to 3, characterized in that: The barrier agent includes an inorganic substance having a layered structure; Preferably, the barrier agent comprises at least one of intercalated montmorillonite, hydrotalcite, talc or kaolin; Preferably, the D50 particle size of the barrier agent is 0.05 to 0.3 μm, and more preferably, the D50 particle size is 0.121 to 0.201 μm.

5. The polyolefin composite material according to any one of claims 1 to 4, characterized in that: The epoxy resin includes an epoxy resin grafted with a carbon-carbon double bond ester compound; Preferably, the carbon-carbon double bond-containing ester compound comprises vinyl acetate and / or ethyl acrylate; Preferably, the grafting rate of the carbon-carbon double bond ester compound grafted onto the epoxy resin is 0.5-2.5%, and more preferably the grafting rate is 1-2%; Preferably, the epoxy resin comprises vinyl acetate grafted epoxy resin and / or ethyl acrylate grafted epoxy resin.

6. The polyolefin composite material according to any one of claims 1 to 5, characterized in that: The mass ratio of the antioxidant, the barrier agent and the epoxy resin is 1:(0.1-2):(0.2-2.5), and more preferably the mass ratio of the antioxidant, the barrier agent and the epoxy resin is 1:(0.3-1):(0.6-1.6); Preferably, the antioxidant includes at least one of a hindered phenol antioxidant, a thioester antioxidant or a phosphite antioxidant.

7. The polyolefin composite material according to any one of claims 1 to 6, characterized in that: The polyolefin composite material further comprises 2 to 16 parts by weight of other additives; Preferably, the other auxiliary agent includes at least one of a compatibilizer, a dispersant or a colorant; Preferably, the compatibilizer comprises maleic anhydride grafted modified metallocene polyethylene; Preferably, the dispersant comprises an organosiloxane polymer; Preferably, the colorant comprises carbon black; Preferably, the polyolefin composite material comprises, by weight, 1 to 6 parts of a compatibilizer, 1 to 6 parts of a dispersant and 0.5 to 3 parts of carbon black.

8. A method for preparing a polyolefin composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The polyolefin composite material is obtained by mixing and extruding an ethylene polymer, an inorganic filler, a barrier agent, an epoxy resin and an antioxidant.

9. The preparation method according to claim 8, characterized in that: The mixed material also includes other additives; Preferably, the extrusion temperature is 180-220°C.

10. A cable, characterized in that: The cable comprises the polyolefin composite material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Cracking-resistant, low-smoke and halogen-free polyolefin cable material and preparation process thereof

    CN106674707A

  • Cracking-resistant, low-smoke and halogen-free polyolefin sheath material for large-cross section electric cable and preparation method of polyolefin sheath material

    CN106995546A

  • Modified polyolefin compound as well as preparation process and application thereof

    CN112812421A

  • B2-grade low-smoke halogen-free polyolefin cable material and preparation method thereof

    CN112940388A

  • Polyolefin composition as well as preparation method and application thereof

    CN115368669A

Cited By

  • Polyolefin composite material and preparation method therefor and use thereof

    WO2026139010A1